A bosentan pharmacokinetic study to investigate dosing regimens in paediatric patients with pulmonary arterial hypertension: FUTURE‐3. (23rd March 2017) - Berger, Rolf M. F.; Gehin, Martine; Beghetti, Maurice; Ivy, Dunbar; Kusic‐Pajic, Andjela; Cornelisse, Peter; Grill, Simon; Bonnet, Damien; ,
Abstract : Aim: The aim of the present study was to investigate whether increasing the bosentan dosing frequency from 2 mg kg –1 twice daily (b.i.d.) to 2 mg kg –1 three times daily (t.i.d.) in children with pulmonary arterial hypertension (PAH) (from ≥3 months to <12 years of age) would increase exposure. Methods: An open‐label, prospective, randomized, multicentre, multiple‐dose, phase III study was conducted. Patients ( n  = 64) were randomized 1:1 to receive oral doses of bosentan of 2 mg kg –1 b.i.d. or t.i.d. The main pharmacokinetic endpoint was the daily exposure to bosentan over 24 h corrected to the 2 mg kg –1 dose (AUC0–24C ). The maximum plasma concentration corrected to the 2 mg kg –1 dose (CmaxC ), the time to reach the maximum plasma concentration (tmax ) and safety endpoints were also assessed. Results: The geometric mean [95% confidence interval (CI)] for AUC0–24C was 8535 h.ng ml –1 (6936, 10 504) and 7275 h.ng ml –1 (5468, 9679) for 2 mg kg –1 b.i.d. and t.i.d., respectively [geometric mean ratio (95% CI) 0.85 (0.61, 1.20)]. The geometric mean (95% CI) for CmaxC was 743 ng ml –1 (573, 963) and 528 ng ml –1 (386, 722) for 2 mg kg –1 b.i.d. and t.i.d., respectively [geometric mean ratio (95% CI) 0.71 (0.48, 1.05)]. The median (range) for tmax was 3.0 h (0.0–7.5) and 3.0 h (1.0–8.0) for 2 mg kg –1 b.i.d. and t.i.d., respectively. The proportions of patients who experienced ≥1 adverse event were similar in the b.i.d. (66.7%) and t.i.d. (67.7%) groups. Conclusions: There appeared to be no clinically relevant difference in exposure to bosentan, or in safety, when increasing the frequency of bosentan dosing from b.i.d. to t.i.d. Therefore, the present study provides no indication that the dosing recommendation should be changed, and 2 mg kg –1 b.i.d. remains the recommended dosing regimen for bosentan in paediatric PAH patients.